2019
DOI: 10.1186/s13690-019-0358-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating carbapenem restriction practices at a private hospital in Manila, Philippines as a strategy for antimicrobial stewardship

Abstract: Background Hospital antimicrobial stewardship programs are especially critical in countries such as the Philippines, where antibiotic resistant infections are highly prevalent. At the study institution in Manila, Philippines, a Prior Approval for Restricted Antimicrobials (PARA) is required for non-infectious disease specialists to prescribe certain antimicrobials, including carbapenems. PARA request forms include specification of empiric or definitive therapy based on diagnostic tests. Recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A study reviewing carbapenem prescriptions in a hospital in Manila observed that 37% were non-compliant to prescription guidelines (Mitchell et al 2019). Policies and strategies to monitor antibiotic resistance and lessen the impact of drivers of antibiotic resistance are needed to mitigate the possible burden brought by these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…A study reviewing carbapenem prescriptions in a hospital in Manila observed that 37% were non-compliant to prescription guidelines (Mitchell et al 2019). Policies and strategies to monitor antibiotic resistance and lessen the impact of drivers of antibiotic resistance are needed to mitigate the possible burden brought by these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Poor antibiotic use practices are also a challenge in health institutions in the Philippines. A retrospective review conducted in the Philippines highlighted that 37% of the prescriptions concerning carbapenem therapy in a private hospital were for non-guideline adherents 7 . Without a proper course of action to address the root problems of AMR, the world will head towards a post-antibiotic era where effective antibiotics cannot treat minor infections 1 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Nonetheless, a recent study evaluating carbapenem restriction practices at a hospital in Manila found that 37% of the carbapenems prescriptions were non-compliant, thus pointing to ongoing challenges in antimicrobial stewardship. 5 Between 2010 and 2014, the Philippine Antimicrobial Resistance Surveillance Program (ARSP) reported increasing resistance rates to antibiotics used to treat P. aeruginosa infections such as carbapenems and extended-spectrum cephalosporins ( Figure 1A-B). In contrast, resistance to aminoglycosides and fluoroquinolones has remained relatively stable or slightly decreased in the same period ( Figure 1C).…”
Section: Introductionmentioning
confidence: 99%